Handbook of School Mental Health Research, Training, Practice, and Policy - Lever, Nancy A.; Bradshaw, Catherine P.; Owens, Julie Sarno; Weist, Mark D. (Issues in Clinical Child Psychology, 2014)
With so few therapeutic outlets readily available to young people, schools have evolved into mental health centers for many students. Yet schools are hampered by limited access to resources needed to provide mental health promotion, prevention, and intervention services. Like its acclaimed predecessor, the Second Edition of the Handbook of School Mental Health offers ways for professionals to maximize resources, make and strengthen valuable connections, and attain more effective school-based services and programming. At the same time, the Handbook provides strategies and recommendations in critical areas, such as workforce development, interdisciplinary collaborations, youth/family engagement, consultation, funding, and policy concerns, summarizes the state of current research, and offers directions for further study. Chapters model best practices for promoting wellness and safety, early detection of emotional and behavioral problems, and school-based interventions for students with anxiety, depression, attention deficit hyperactivity disorder, and other common challenges. In spotlighting this range of issues, the contributors have created a comprehensive game plan for advancing the field. Among the Handbook's topics: Pre-service training for school mental health clinicians. Cognitive-behavioral interventions for trauma in schools. Increasing parental engagement in school-based interventions. Models of psychiatric consultation to schools. Culturally competent behavioral and emotional screening. Bullying from a school mental health perspective. Prevention and intervention strategies related to a variety of mental health problems in schools. The Second Edition of the Handbook of School Mental Health is an essential reference for researchers, graduate students, and other professionals in child and school psychology, special and general education, public health, school nursing, occupational therapy, psychiatry, social work and counseling, educational policy, and family advocacy.